Lower socioeconomic status among men in relation to the association between job strain and blood pressure - Landsbergis, Paul A.; Schnall, Peter L.; Pickering, Thomas G.; Warren, Katherine; Schwartz, Joseph E. (Scandinavian Journal of Work, Environment & Health, 2003)
' ' OBJECTIVES ': 'This study attempted to determine whether the association between job strain (high job demands plus low job control) and blood pressure among men varies by socioeconomic status. ' ' METHODS ': 'The cross-sectional associations between job strain and ambulatory blood pressure, by level of education, occupational status, and income, and the interaction between job strain and these measures of socioeconomic status were assessed by multiple linear regression, adjusted for age, race or ethnicity, body mass index, alcohol use, smoking, standing position, and worksite for 283 men, aged 30-60 years, from eight worksites in New York City. ' ' RESULTS ': 'A substantial association between job strain and work ambulatory blood pressure was found among men with lower socioeconomic status, ranging from 2.7-11.8 mm Hg systolic to 1.9-6.1 mm Hg diastolic blood pressure, depending upon the measure of socioeconomic status examined. However, in the groups with high socioeconomic status, the association between job strain and ambulatory blood pressure at work was much smaller, the range in blood pressure being 0-5.3 (systolic) and 0.2-2.1 (diastolic) mm Hg. Two of the 10 tests of the interaction between job strain and socioeconomic status had a P-value of <0.05. ' ' CONCLUSIONS ': 'These data provide evidence that the relationship of job strain with blood pressure is greater among men with lower socioeconomic status.
Keywords: blood pressure; hypertension; job strain; job stress; man; social class; socioeconomic status